NOVA HARO IN SAGITTARIUS AND SCORPIUS - TABOADA, DOMINGO (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
The light curves of a Nova in Sagittarius (Harvard announcement Card No. 1166) and of a Nova in Scorpius (Harvard announcement Card No. 1167) are given. Table I.- Visual magnitudes observed of the Nova in Sagittarius. Table II.- Visual magnitudes observed
BOL OBS TONAN TACUB
Keywords: NOVA HARO, SAGITTARIUS, SCORPIUS; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; ASTRONOMIA DE POSICION